Enhancing Informed Consent Forms for Medical Devices: International Regulatory Guidance and Ethical Recommendations - Peycheva OM; Ainsworth LR; Fujimori-Petrikova G; Lee WT (Medical Devices: Evidence and Research)
Olga Marius Peycheva, Lydia R Ainsworth, Galina Fujimori-Petrikova, Wai Theng Lee Solutions OP Ltd, Dover, UKCorrespondence: Olga Marius Peycheva, Solutions OP Ltd, 74 Pencester Road, Dover, CT16 1BW, UK, Email olga.peycheva@solutionsop.co.ukAbstract: Many developers of medical devices face a new reality with the increasing demand for clinical evidence that is generated by clinical investigations. This affects biotechnology companies, start-ups and academic research centres. The participants’ informed consent form (ICF), which includes the participant information sheet (PIS), is among the critical documents that are part of the clinical investigation. While many countries around the world follow the principles of good clinical practice (GCP), there are country-specific variations of the ICF requirements. In addition, many of the country guidelines are focused on medicinal products rather than medical devices. Clinical investigations involving medical devices have their unique challenges and need additional guidance to help developers improve the ICF and PIS content. This review provides information on the latest regulatory recommendations from Europe, USA and Asia regarding the content of the ICF and offers practical advice from professionals experienced in preparing ICFs. It also includes some ethical considerations that must be taken into account.Keywords: informed consent, medical devices, GCP